PENGARUH MEDIA PEMBELAJARAN FLASHCARD TERHADAP KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS 1 SD MUHAMMADIYAH SIJABUT - Jumiatik, Jumiatik; Wahyuni, Nur; Panggabean, Sartika (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This study aims to determine the effect of Flashcard learning media on the early reading ability of first-grade students at SD Muhammadiyah Sijabut. The background of this research stems from the low early reading skills of students due to the lack of variation in learning media and low learning motivation. This research employed a quantitative method using a Quasi-Experimental design of the Nonequivalent Control Group Design type. The research subjects consisted of two classes, the experimental and control groups, each with 25 students. The experimental class received instruction using Flashcard media, while the control class used conventional learning methods. Data were collected through early reading tests covering the ability to recognize letters, read syllables, words, phrases, and simple sentences. The data were analyzed using a t-test to determine significant differences between the two groups. The results showed a significant improvement in early reading ability in the experimental class compared to the control class. Therefore, it can be concluded that Flashcard learning media has a positive and significant effect on improving the early reading skills of first-grade students at SD Muhammadiyah Sijabut. Keywords: early reading ability, elementary school, flashcard, learning media. Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh media pembelajaran Flashcard terhadap kemampuan membaca permulaan siswa kelas 1 SD Muhammadiyah Sijabut. Latar belakang penelitian ini berangkat dari rendahnya kemampuan membaca permulaan siswa yang disebabkan oleh kurangnya variasi media pembelajaran dan rendahnya motivasi belajar siswa. Penelitian ini menggunakan metode kuantitatif dengan desain Quasi Experimental jenis Nonequivalent Control Group Design. Subjek penelitian terdiri dari dua kelas, yaitu kelas eksperimen dan kelas kontrol, masing-masing berjumlah 25 siswa. Kelas eksperimen diberikan perlakuan pembelajaran dengan media Flashcard, sedangkan kelas kontrol menggunakan pembelajaran konvensional. Data diperoleh melalui tes membaca permulaan yang mencakup kemampuan mengenal huruf, membaca suku kata, kata, frasa, dan kalimat sederhana. Analisis data dilakukan dengan uji statistik menggunakan t-test untuk mengetahui perbedaan signifikan antara kedua kelompok. Hasil penelitian menunjukkan adanya peningkatan kemampuan membaca permulaan yang signifikan pada kelas eksperimen dibandingkan kelas kontrol. Dengan demikian, dapat disimpulkan bahwa media pembelajaran Flashcard berpengaruh positif dan signifikan terhadap peningkatan kemampuan membaca permulaan siswa kelas 1 SD Muhammadiyah Sijabut. Kata kunci: flashcard, kemampuan membaca permulaan, media pembelajaran, sekolah dasar.